Long-term follow-up of MRD-guided ibrutinib plus venetoclax in relapsed CLL: phase 2 VISION/HO141 trial - Carsten U. Niemann; Julie Dubois; Kazem Nasserinejad; Caspar da Cunha-Bang; Sabina Kersting; Lisbeth Enggaard; Gerrit J. Veldhuis; Rogier Mous; Clemens H.M. Mellink; Anne-Marie F. van der Kevie-Kersemaekers; Johan A. Dobber; Christian B. Poulsen; et al. (Blood Advances, 2025)
Abstract: Patients with relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL) are treated with fixed-duration B-cell lymphoma 2 inhibitors + CD20 monoclonal antibodies or continuous Bruton tyrosine kinase (BTK) inhibitors. Although continuous treatment may lead to cumulative toxicity or resistance, fixed-duration treatment may lead to undertreatment and early relapse. Efficacy and safety of minimal residual disease (MRD)-guided treatment cessation of ibrutinib + venetoclax (I+V) with reinitiated I+V upon MRD conversion was evaluated in the randomized VISION/HO41 phase 2 study. Four-year follow-up including long-term toxicity and MRD kinetics are reported. Patients received ibrutinib for 2 (28-day) cycles followed by 13 cycles of I+V. Patients reaching undetectable MRD at 4 years (<10−4, flow cytometry) in the blood and bone marrow at cycle 15 (C15) were randomized 2:1 between treatment cessation with reinitiated I+V upon detectable MRD2 (dMRD2; sensitivity of ≥10−2 by flow cytometry) and ibrutinib maintenance. MRD4-positive patients at C15 remained on ibrutinib (dMRD4 arm, defined by MRD sensitivity of ≥10−4 by flow cytometry). With a median of 51.7 months, the estimated 4-year overall survival (OS) was 88%, progression free survival (PFS) was 81%; 14% of patients required next-line treatment (NT). For patients randomized to treatment cessation, 40% had reinitiated therapy per protocol because of dMRD2. No difference between treatment cessation, ibrutinib maintenance, or the dMRD4 arm continuing ibrutinib was seen for OS, PFS, or NT in landmark analysis from C15 time of randomization. Lower toxicity was demonstrated for the treatment-cessation arm. MRD-guided cessation and reinitiation of I+V for R/R CLL is feasible, reduces toxicity compared with indefinite BTK inhibitor, while providing comparable PFS rates. This trial was registered at www.clinicaltrials.gov as #NCT03226301.